THE ROLE OF THE TECHNOLOGICAL INNOVATION CENTER IN THE TRANSFER OF CLEANER TECHNOLOGIES IN THE FACE OF THE CARBON ADJUSTMENT MECHANISM AT THE EUROPEAN UNION BORDER - Bonfim, Thais Farias de Oliveira; de Souza, André Luis Rocha; Andrade, José Célio Silveira (Seven Editora, 2026)
This research aimed to analyze the role of Technological Innovation Centers (NITs), linked to Scientific, Technological and Innovation Institutions (ICTs), as drivers of cleaner technology development in the steel sector, considering the possibilities of technology transfer to adapt the sector to the requirements of the European Union Border Carbon Adjustment Mechanism (CBAM). The research has a qualitative approach, with bibliographic and documentary analyses on carbon emissions in the industrial sector, conventional technologies used in steelmaking, and cleaner technologies applicable to the steel sector. The results pointed to new routes for cleaner technologies for decarbonization and the importance of NITs in mediating between scientific production and the productive sector for the development of technologies in ICTs that can contribute to solving economic and environmental problems that help achieve global decarbonization goals and meet the requirements imposed by the CBAM. In conclusion, it can be said that there is a risk that Brazilian companies exporting steel products will lose competitiveness in the European market if strategies are not adopted to overcome the challenges imposed by carbon restriction policies on products that do not meet CBAM criteria.DOI: https://doi.org/10.56238/sevened2026.008-102